Novel Suara Samudra Karya Maria Matildis Banda: Kajian Psikologi - Apridayanti, Ni Made Meri; Cika, I Wayan; Sudewa, I Ketut (Humanis, 2020)
This research is titled "Novel Suara Samudra by Maria Matildis Banda Psychology Psychology Study". The following research aims to find out the structure and relationship between psychology figures contained in the novel. There are three theories used for this research, namely structural theory based on Stanton's opinion, the theory of literary psychology by Sigmund Freud, the theory of love from Sternberg. The method used in data collection is a literature study method with advanced techniques in the form of note and write techniques. Then proceed with using the formal method and descriptive analysis method for analyzing data. Furthermore, in presenting the results of the analysis using the description method. Based on the analysis that has been done on the novel Suara Samudra, several things were discovered. First, in the analysis of the structure which included the characterizations, plot and setting depicted in the novel Suara Samudra. Second, the psychological relationship that is seen in terms of conflicts that occur between characters in the novel Suara Samudra.